Evaluation of the association of birth order and group childcare attendance with Kawasaki disease using data from a nationwide longitudinal survey - Namba, Takahiro; Takeuchi, Akihito; Matsumoto, Naomi; Tsuge, Mitsuru; Yashiro, Masato; Tsukahara, Hirokazu; Yorifuji, Takashi (Frontiers in Pediatrics, 2023)
Abstract Background: Kawasaki disease (KD) is a form of pediatric systemic vasculitis. Although the etiology remains unclear, infections have been identified as possible triggers. Children with a later birth order and those who attend childcare are at a higher risk of infections due to exposure to pathogens from their older siblings and other childcare attendees. However, longitudinal studies exploring these associations are limited. Thus, we aimed to elucidate the relationship between birth order, group childcare attendance, and KD, using a nationwide longitudinal survey in Japan. Methods: In total, 36,885 children born in Japan in 2010 were included. The survey used questionnaires to identify hospitalized cases of KD. We evaluated the relationship between birth order classification, group childcare attendance, and KD prevalence every year, from 6 to 66 months of age. For each outcome, odds ratios (ORs), and 95% confidence intervals (CIs) were estimated after adjusting for child factors, parental factors, and region of residence. Results: Children with higher birth orders were more likely to be hospitalized with KD at 6–18 months of age (second child OR: 1.77, 95% CI: 1.25–2.51; third child OR: 1.70, 95% CI: 1.08–2.65). This trend was stronger for children who did not attend group childcare (second child OR: 2.51, 95% CI: 1.57–4.01; third child OR: 2.41, 95% CI: 1.30–4.43). An increased risk of KD hospitalization owing to the birth order was not observed in any age group for children in the childcare group. Conclusions: Children with higher birth orders were at high risk for hospitalization due to KD at 6–18 months of age. The effect of birth order was more prominent among the children who did not attend group childcare.